MAGNETIC RESONANCE IMAGING BASED MORPHOMETRIC ASSESSMENT OF GLENOID - Kekatpure, Dr. Aashay; Manoj, Megha; Kashikar, Dr. Shivali; Kekatpure , Dr. Aditya (Acta medicae Medianae, 2024)
This study aimed to evaluate the morphological variations of the glenoid in an Asian population and compare them with those in the Western population. A retrospective study of 100 patients who presented with shoulder pain between Jan. 2018 and Jan. 2019 was done. The glenoid height, width and version were measured on coronal and axial images. The overall mean version was found to be an anteversion of 0.40 ± 3.6. The average glenoid widths in males and females were 29 mm and 25.2 mm respectively, whereas the overall average glenoid width was 27 ± 3.2 mm. The average glenoid heights in males and females were 35.7 mm and 32.4 mm respectively, whereas the overall average glenoid height was 34 ± 2.5 mm. The glenoid dimensions in the Asian population were found to be slightly less than the ones in the Western population. This difference has to be considered when choosing a prosthesis for shoulder arthroplasty.
Keywords: glenoid, magnetic resonance imaging, arthroplasty, central India